Эколого-фаунистический обзор жужелиц рода Chlaenius В о n. (Coleoplera, Carabidae) Украины - Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1971)
18 species of ground-beetles from the genus Chlaenius are mentioned for the Ukraine. Their zoogeographical characteristic is given. The distribution of the ground-beetles in the investigated territory, distribution under conditions of natural and cultural hiolopes, diurnal and seasonal dynamics, nutrition are considered. Their enemies and parasites are staled. New occurrences of these beetles in the Ukraine are given.